OPTIMIZATION OF POLYMER AGGREGATE WITH SAND AND ASPHALT MIX FOR ROAD POTHOLES REPAIR - Heri Sujatmiko (International Journal of Multidisciplinary Research and Literature, 2022)
The roads in Banyuwangi city have sustained considerable damage; the asphalt supply has yet to meet the need because 45% of the roads are built using gravel and soil. Another problem is related to plastic, a type of waste that is difficult to recycle. To solve these two problems, we conducted research in making polymer-modified asphalt by utilizing food packaging plastic waste. The process followed the standard specification of Highway Construction Division 6, revision 3: the polymer blending process was performed when the hot asphalt mixing temperature was 145°C- 155°C. The research results found that the variation of asphalt content used in the mixture was 4.5%, 5%, 5.5%, and 6%. Moreover, the optimal asphalt content was 5.3%. The polymer was mixed with the optimal asphalt content of 0%, 1%, 2%, 3%, and 4%. The test results showed that the optimal polymer content was 0.5%, with a maximum of 1%. Polymer-modified asphalt had a high stability value of 23.64% greater than conventional. In addition, the air cavity value in the mixture was 5.74% greater than conventional asphalt. The discovery of this mixture of materials is very appropriate for sustainable road construction in Indonesia.